Interpretasi Kritisisme Immanuel Kant dalam Budaya Jawa Modern - Benny Baskara (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
This essay purposed to make interpretation about critisism, in this case critical thinking process on Modern Javanese Culture. Critical thinking actually can reveral the ancient and traditional Javanese values into reasonable and scientific explanations. This process create many advantages for the development of Javanese Culture, especially the change from traditional to modern. Javanese people start with modern lifestyle which critical thinking as